RETRACTED: Colonic flora, Probiotics, Obesity and Diabetes - Marik, Paul E. (Frontiers in Endocrinology, 2012)
Obesity results from alterations in the body's regulation of energy intake, expenditure, and storage. Animal and human data demonstrate that phylogenic changes occur in the microbiota composition in obese individuals. Furthermore, evidence from animal models suggest that the alterations of the gut microbiota with obesity results in increased energy extraction and lipid deposition, altered release of entero-hormones, increased intestinal permeability and metabolic endotoxemia. Treatment with pre- and probiotics may reverse many of metabolic effects linked with the altered microbiota in obese patients. The gut microbiota is, therefore, a potential nutritional and pharmacological target for the management of obesity and obesity-related disorders.